Investigation into the beneficiation potential of a low-grade discard coal from the Witbank coalfield - Nyoni, Sancho Nkosilathi (My University, 2019)
The South African Department of Energy has projected that the usable coal reserves will have depleted within hundred years. This research, in response to the problem, investigated the possibility of expanding the coal resource through beneficiation of low grade discard coal from the Witbank Coalfield. Amenability to beneficiation was investigated using various analytical tools and through sink float testing, and flotation separation techniques. Sink-float testing showed that the coal is highly difficult to wash through most gravity methods but indicated that it was amenable to separation using dense medium cyclone DMC equipment.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science to the Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical, University of the Witwatersrand, 2019